2024
DOI: 10.1038/s41522-024-00488-7
|View full text |Cite
|
Sign up to set email alerts
|

How probiotics, prebiotics, synbiotics, and postbiotics prevent dental caries: an oral microbiota perspective

Si-Chen Luo,
Si-Min Wei,
Xin-Tao Luo
et al.

Abstract: Dental caries, a highly prevalent oral disease, impacts a significant portion of the global population. Conventional approaches that indiscriminately eradicate microbes disrupt the natural equilibrium of the oral microbiota. In contrast, biointervention strategies aim to restore this balance by introducing beneficial microorganisms or inhibiting cariogenic ones. Over the past three decades, microbial preparations have garnered considerable attention in dental research for the prevention and treatment of dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 193 publications
0
6
0
Order By: Relevance
“…The focus of the present review is solely on the effect of probiotic supplements on the oral microbiota, which is why studies on prebiotics, synbiotics, and postbiotics were not included. However, it is important to stress that studies have demonstrated the potential of using prebiotics such as arginine and non-cariogenic sugars in the prevention of dental caries [120,121], as well as dietary fibers in the prevention of periodontitis [122], thereby illuminating a preventive potential of prebiotics in oral care.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of the present review is solely on the effect of probiotic supplements on the oral microbiota, which is why studies on prebiotics, synbiotics, and postbiotics were not included. However, it is important to stress that studies have demonstrated the potential of using prebiotics such as arginine and non-cariogenic sugars in the prevention of dental caries [120,121], as well as dietary fibers in the prevention of periodontitis [122], thereby illuminating a preventive potential of prebiotics in oral care.…”
Section: Discussionmentioning
confidence: 99%
“…In the oral cavity, a variety of prebiotics have been investigated. These include some sugars, sugar alcohols, oligosaccharides (complex sugars), amino acids, and nitrogen species ( Luo et al, 2024 ). Prebiotics must be carefully selected to encourage the growth of probiotic strains without stimulating the growth of oral pathogens.…”
Section: Prebiotics and Postbioticsmentioning
confidence: 99%
“…They also have the ability to inhibit their growth by producing antimicrobial peptides, and some probiotics may participate in the indirect elimination of pathogens by stimulating the host's immune system through cytokine overexpression, which leads to a higher phagocytic activity. Due to the aforementioned factors, probiotics have been considered an effective option to reduce the incidence of infections produced by pathogenic biofilms [5,13,16,17].…”
Section: Introductionmentioning
confidence: 99%